2019
DOI: 10.1039/c8en00933c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating environmental risk assessment models for nanomaterials according to requirements along the product innovation Stage-Gate process

Abstract: A quantitative approach to matching existing environmental assessment models to the needs of stakeholders at different stages during innovation of nanomaterials and nano-enabled products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Our review identified thirty-six (36) tools in this “Risk and concern/safety assessment” category (Table 3). Hristozov et al [7], Sørensen et al [63] and Oosterwijk et al [64] comprehensively reviewed most of such tools for MNs. Therefore, we mainly complement their work by focusing on the risk communication aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Our review identified thirty-six (36) tools in this “Risk and concern/safety assessment” category (Table 3). Hristozov et al [7], Sørensen et al [63] and Oosterwijk et al [64] comprehensively reviewed most of such tools for MNs. Therefore, we mainly complement their work by focusing on the risk communication aspects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hristozov et al [62] have detailed the range of different risk pre-assessment and evaluation methods available, Lombi et al [63] addressed risk governance in the agriculture-nanotechnology field, while Grieger et al [64] have detailed the bevy of tools for risk screening of NMs. Similarly, Subramanian et al [65] and Isigonis et al [66] reflected upon tools for nanotechnology risk communication and mitigation, Trump et al [67] presented six options that have been deployed to address uncertainty regarding NMs in the United States, the European Union, as well as in developing countries, while Sørensen et al [68] evaluated environmental risk assessment models for NMs, in relation to their applicability within the caLIBRAte product innovation framework for NMs risk governance.…”
Section: Moving From Risk Assessment and Management To Governance Of mentioning
confidence: 99%
“…This problem is addressed in numerous research projects developing Decision Support Systems for nanomaterials. [ 10–12 ]…”
Section: The Science Policy Problems Addressed By Riskgonementioning
confidence: 99%